Diagnóstico molecular da leishmaniose tegumentar americana em pacientes atendidos no Centro de Referência em hanseníase e dermatologia sanitária da Universidade federal de Uberlândia, CREDESH-UFU. - Silva, Fernanda Cristina Assis (2017)
Leishmaniasis represents a complex of parasitic diseases with high rates of morbimortality which are extremely associated with poverty .The definitive diagnosis of ATL is based on clinical and epidemiological data associated to the laboratory diagnosis. PCR has proved to be a valuable tool in the diagnosis of leishmaniasis, because it is a faster and more sensitive than conventional methods, and can identify the species in different clinical samples. The objective of this study was to evaluate the efficacy of PCR for the diagnosis of ACL, to identify Leishmania species in samples from patients attended by the National Reference Center on Leprosy and Sanitary Dermatology, Federal University of Uberlândia. A total of 37 skin samples collected from patients with skin lesions suggestive of ATL and four suspects were submitted to the diagnosis of IHQ and PCR and subsequent PCR-RFLP analysis of positive samples. A total of 37 skin samples collected from patients with cutaneous lesions suggestive of ATL were submitted to IHC and PCR diagnosis, following by PCR-RFLP analysis of positive samples. Ten samples positive for leprosy and negative for Leishmania (Montenegro Skin test and IHC negative results) were used for test the absence of primers annealing with Mycobacterium leprae. By consensus a result was considered as positive when at least three of the five diagnostic techniques tested were positive, resulting in 30 (73%) samples considered positives and 11 as negative (27%). IHC showed the lower sensitivity and NPV when compared with the other three PCR tests, but it showed high specificity and PPV. The values of the sensitivity, specificity, PPV and NPV for the primers 13A/13B and L150/152 were 80% and 100%, and 90% and 100%, 100 and 100%, 50% and 66.6%, respectively. The primers HSP70 and LITS1/L5.8S present similar results reaching 100% of sensitivity, specificity, NPV and PPV. The four PCR assays presented better results for ATL diagnosis when compared to the IHC and the others methods routinely used. The identification of species through PCR-RFLP was able to identify the four species proposed in this study L.braziliensis, L. amazonensis, L.guyanensis and L.infantum. In conclusion, ITS1 and HSP70 PCR-RFLP assays were able to diagnosing to identify the ATL causative agent with high sensitivity and specificity, however, the HSP70 PCR-RFLP showed better applicability in the diagnostic routine of ATL in Brazil due to its high sensitivity, specificity and operational characteristics.